Indexicais descritivos: uma investigação semântico-pragmática - Dal Ava, Felipe Manca (Universidade Federal de São Carlos, 2018)
In this dissertation, we will present a general introduction with some of the main ideas involving indexicals, and briefly touching the problem of their descriptive readings (descriptive indexicals). We will focus, in particular, on the general characteristics of Kaplanian theory (1989) and see some alternate theories (Hunter, Nunberg, Elbourne, etc.) that might add up and define how indexicals might behave. Soon after it, in the first chapter, we will present Kaplan's theory (1989) in its details, focusing mainly on the indexicals; specially on how Kaplanian functions (character and content) works, as well as scope and limitations of this kind of approach. In the second chapter, the longest of our work, we will highlight the main alternatives to Kaplanian theory, notably those that might consider descriptive readings of indexicals as viable. We will explore each one of those alternatives (Nunberg, Elbourne, Hunter, Kijania-Placek, Sæbø) and work with different examples and possible solutions to this linguistic problem. In the third and final chapter, we will take into account all theories presented and consider their advantages and disadvantages when dealing with descriptive indexicals.
Descriptive indexicals: a semantic-pragmatic study
Keywords: Indexicais; Indexicais descritivos; Semântica; Pragmática; Epistemologia; Indexicals; Descriptive indexicals; Semantics; Pragmatics; Epistemology; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA